Relationship between Energy Intake and Diarrhea with Stunting Incidence in Children Age 0-59 Months in Lhokseumawe City - Fakhrizawaty, Zuhra; Sudaryati, Etti; Aritonang, Evawany Y. (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The research objective is analysis of relationship between energy intake and diarrhea with stunting incidence in children age 0-59 months in Lhokseumawe City. This research is an observational study using a cross sectional design. Population of this study is children age 0-59 months who are in Lhokseumawe City which is 8,025 people. Sample in this study amounted to 199 children age 0-59 months. Data on nutrient intake was obtained using a food recall form, while direct data related to infectious diseases and stunting were obtained using a questionnaire. This study uses bivariate analysis. Bivariate analysis is performed using chi-square test. The results show that there is a significant relationship between energy intake and diarrhea with stunting incidence in children age 0-59 months in Lhokseumawe City.